Expression of some Serine Protease Encoding Genes and Trypsin-like Protease Activity in Black Tiger Shrimp (Penaeus monodon) Infected with White Spot Syndrome Virus - Thai, Le The; Thai, Quach Hong; Loan, Nguyen Thi Hong (VNU Journal of Science: Natural Sciences and Technology; Vol 38 No 3DO - 10.25073/2588-1140/vnunst.5491, 2022)
In this study, trypsin-like protease activity and expression of serine protease encoding genes (PmPPAE1, PmPPAE2 - clip-serine proteases and PmTLP1, PmTLP2 - trypsin-like proteases) in the different tissues of black tiger shrimp were determined. The expression level of PmPPAE1 and PmPPAE2 was the highest in the hemolymph; meanwhile that of PmTLP1 and PmTLP2 was the highest in the hepatopancreas. In the hemolymph of white spot syndrome virus (WSSV)-injected shrimp, the expression of PmPPAE1, PmPPAE2 and PmTLP2 genes was upregulated by 2.32, 2.57 and 4.56-folds, respectively, whereas the expression of PmTLP1 was downregulated by 1.47-folds relative to the control group (injected with phosphate buffered saline). In the hepatopancreas of WSSV-injected shrimp, the expression levels of PmPPAE1, PmPPAE2 increased by 2.24 and 3.99-folds, respectively, and that of PmTLP1 and PmTLP2 decreased by 1.51, 1.29-folds, respectively. Trypsin-like protease activity was found increased 3.25-fold and decreased 4.1-fold, in the hemolymph and hepatopancreas of WSSV-infected shrimp, respectively. These data indicate the role of serine proteases in immune response of the shrimp.